Aspirations in rural Pakistan - Kosec, Katrina; Hausladen, Stephanie; Khan, Huma (International Food Policy Research Institute, 2014)
Understanding the role that aspirations play in promoting growth requires an understanding of where aspirations come from and how they can be raised through policy. A recent IFPRI report, “Aspirations in Rural Pakistan: An Empirical Analysis,” uses the 2012 Pakistan Rural Household Panel Survey (RHPS) data to study the aspirations of over 3,500 men and women in rural Pakistan. The analysis explores aspirations of four types: income, wealth, education, and social status. The report concludes that particular groups—especially women, the uneducated, and agricultural wage laborers—have especially low aspirations. Higher aspirations are associated with a number of behaviors and productive investments that may fuel growth, such as higher crop yields, more intensive input use, and greater use of credit. The analysis suggests three major areas in which policy might raise aspirations in rural Pakistan. These include policies that: (a) improve perceptions of access to justice and increase the involvement of citizens in decision-making; (b) improve community infrastructure and other amenities; and (c) efficiently target social protection programs—especially in the aftermath of economic shocks like Pakistan’s 2010 floods.